2007
DOI: 10.1038/modpathol.3800733
|View full text |Cite
|
Sign up to set email alerts
|

Loss of membranous Ep-CAM in budding colorectal carcinoma cells

Abstract: Tumor budding is a histological feature that reflects loss of adhesion of tumor cells and is associated with locoregional metastasis of colorectal carcinoma. Although nuclear localization of b-catenin is associated with tumor budding, the molecular mechanism remains largely elusive. In this study, we hypothesize that the epithelial cell adhesion molecule (Ep-CAM) is involved in tumor budding. In order to address this question, we performed immunohistochemistry on Ep-CAM using three different antibodies (monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
99
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 38 publications
12
99
0
Order By: Relevance
“…In the present study, loss of membranous epcam staining was associated w ith poorly differentiated tumours and poor survival. Those findings are similar to results from other studies 6 . Recent studies have proposed that the proteolytic cleavage of epcam-icd triggers a signalling cascade leading to the activation of the Wnt/ beta-catenin pathway 3 .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In the present study, loss of membranous epcam staining was associated w ith poorly differentiated tumours and poor survival. Those findings are similar to results from other studies 6 . Recent studies have proposed that the proteolytic cleavage of epcam-icd triggers a signalling cascade leading to the activation of the Wnt/ beta-catenin pathway 3 .…”
Section: Discussionsupporting
confidence: 83%
“…Expression of epcam has been observed in various epithelial neoplasms, including gastrointestinal, thyroid, kidney, prostate, breast, and lung carcinomas 6,7 , leading to its selection as a target for immunotherapy. The human anti-epcam antibody adecatumumab and the murine monoclonal antibody edrecolomab were developed in hope that they could be used in targeted cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has a role as an adhesion molecule that suppresses metastasis by holding cells in place (Basak et al, 1998), while induces dissociation of cadherin-mediated adhesion to promote invasion and metastasis (Gumbiner, 1996;Litvinov et al, 1997). For example, Gosens et al (2007) reported that Ep-CAM expression decreased in budding part of colorectal cancer and Rao et al (2005) reported that Ep-CAM expression was lower in circulating tumors cells compared with their corresponding primary tumors. The significance of Ep-CAM expression in pancreatic cancer H Akita et al…”
Section: Discussionmentioning
confidence: 99%